Nutrient Status and Mycorrhizal Population on Various Food Crops Grown Following Corn Inoculated with Indigenous Mycorrhiza on Sandy Soil of North Lombok, Indonesia - Wahyu Astiko; Muhammad Taufik Fauzi; . Sukartono (UNIVERSITY OF LAMPUNG, 2015)
This study was aimed to determine the nutrient status and population of arbuscular mycorrhizal fungi (AMF) on the second cropping cycle of corn-based cropping patterns which utilized indigenous mycorrhizal fungi on sandy soil. The experiment was conducted at the Akar-Akar village in Bayan district of North Lombok, in a Randomized Block Design, with 4 replications and 6 treatments of cropping cycles (P0 = corn-soybean as a control, in which the corn plants were not inoculated with AMF; P1 = corn-soybean, P2 = corn-peanut, P3 = corn-upland rice, P4 = corn-sorghum, and P5 = corn-corn, in which the first cycle corn plants were inoculated with AMF). Results indicated that the status of N, P, K and organic-C increased significantly up to 112%, 148%, 88%, 88% at 60 DAS and 66%, 135%, 54%, 60% at 100 DAS, respectively in the second cropping cycle of sorghum compared to control. Uptake of N, P, K and Ca the sorghum plants at 60 DAS of the second cropping cycle reached 200%; 550%; 120% and 490%, respectively a higher than in the control. Mycorrhizal populations (spore number and infection percentage) were highest in the second cycle sorghum, achieving 335% and 226% respectively, which were significantly higher than those in the control.